The Infrastructure for Sustainable Mobility. - Mazzoncini, Renato; Somaschini, Claudio; Longo, Michela (Springer, 2020)
The objective of this chapter is to indicate in which direction cities must invest in order to become smart and sustainable in terms of mobility. On the basis of the current trends and considering technological innovation in the mobility sector, the chapter will address those aspects which the planners will have to take into account not only in the design of the new neighbourhoods, but also in the redevelopment of the recovery of the existing ones. The authors discuss both collective mobility and individual mobility, thus ranging from underground railways to electric scooters. In the final part, general criteria for sustainable mobility planning are provided.
Keywords: Nachhaltige Mobilität; Stadtverkehr; Stadtneubau; Integrierte Planung; Stadterneuerung; Verkehrsinfrastruktur; Infrastrukturverbesserung; Öffentlicher Verkehr; Individualverkehr; Elektromobilität; E-Scooter; Mikromobilität